2010
DOI: 10.1186/1471-2334-10-273
|View full text |Cite
|
Sign up to set email alerts
|

Rv1985c, a promising novel antigen for diagnosis of tuberculosis infection from BCG-vaccinated controls

Abstract: BackgroundAntigens encoded in the region of difference (RD) of Mycobacterium tuberculosis constitute a potential source of specific antigens for immunodiagnosis. In the present study, recombinant protein Rv1985c from RD2 was cloned, expressed, purified, immunologically characterized and investigated for its potentially diagnostic value for tuberculosis (TB) infection among BCG-vaccinated individuals.MethodsT-cell response to Rv1985c was evaluated by IFN-γ ELISPOT in 56 TB patients, 20 latent TB infection (LTBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Our result suggested that the sensitivity of the QFT-IT assay could be raised when it was used in combination with Rv1985c pool2 and Rv1985c pool4 , just as previous studies did (10,16,17). Though the additive effect on sensitivity was not statistically significant, the trend may be more obvious and relevant if tested on a broader scale.…”
Section: Differentiation Of M Tuberculosis Infection In Bcg-vaccinatedmentioning
confidence: 50%
See 4 more Smart Citations
“…Our result suggested that the sensitivity of the QFT-IT assay could be raised when it was used in combination with Rv1985c pool2 and Rv1985c pool4 , just as previous studies did (10,16,17). Though the additive effect on sensitivity was not statistically significant, the trend may be more obvious and relevant if tested on a broader scale.…”
Section: Differentiation Of M Tuberculosis Infection In Bcg-vaccinatedmentioning
confidence: 50%
“…PHA (2.5 g/ml) and saline were added as a positive control and a negative control, respectively. Peptide cocktails from ESAT-6, including ESAT-6 from residues 1 to 20 (ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ), ESAT-6 42-65 , ESAT-6 52-75 , and ESAT-6 72-95 , were selected according to some other research (23,24) and tested as controls to evaluate the diagnostic performance of the selected peptide pools. On the basis of a dose-response curve ranging from 0 to 20 g/ml, the working concentration of the peptide mixtures was determined at the concentration with the strongest response, which was 1 g/ml per peptide.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations